Opportunities and barriers for the use of Australian cancer registries as platforms for randomized clinical trials. Issue 4 (23rd November 2021) - Yan, Mabel K.; Adler, Nikki R.; Heriot, Natalie; Shang, Catherine; Zalcberg, John R.; Evans, Sue; Wolfe, Rory; Mar, Victoria J.
Abstract: It is well recognized that randomized controlled trials (RCTs) are a powerful tool to investigate causal relationships, and are considered the gold standard level of research evidence. However, RCTs can be expensive and time‐consuming, and when they employ strict eligibility criteria, it results in an unrepresentative population and limited external validity. Recently, the registry‐based randomized clinical trial (RRCT) has emerged as an alternative trial design. Utilizing registries to underpin such studies, RRCTs can have advantages including rapid recruitment, and enhanced generalizability. In Australia, legislated mandatory reporting of cancer diagnoses means that jurisdictional cancer registries are a rich source of systematically collected patient details, representing sound platforms for comprehensive data capture that can serve as a key tool for further research. We review the roles of cancer registries in Australia, discuss important considerations relevant to the design of RRCTs, and outline the opportunities provided by cancer registries to strengthen cancer research.